Kehadiran Orang India di Jawa: Tinjauan Data Prasasti Abad XI–XV Masehi - Nufus, Asri Hayati (Penerbit BRIN (BRIN Publishing), 2024)
Abstract, The Presence of Indians in Java: Review from the Eleventh to Fifteenth Centuries AD Inscriptions. The relationship between Nusantara and foreigners has been established since the early centuries AD. One of the groups that arrived was the Indians. This later influenced the development of Hindu-Buddhist history in Nusantara. Their presence was first explicitly recorded in the Cane inscription during the reign of Airlangga in the 11th century AD and continued through the Majapahit period in the 15th century AD. These records indicate a close and enduring relationship between India and Java. This study aims to understand the influence of Indian culture on the social, economic, and political development in Java during this period, as well as to identify the origins of the Indian communities, their motives for coming to Java, and the regulations implemented by the Javanese kingdoms as reflected in the inscriptions. The research employs a descriptive-analytical method with a qualitative approach, encompassing the collection, analysis, and interpretation of inscriptions from the 11th to the 15th centuries AD. The findings reveal that ancient Javanese inscriptions mentioned various Indian groups such as kling, āryya, dravida, pandikira, karnnataka/karnnake, malyala, and cwalika. The role of juru kling is also identified, as responsible for managing the kling people and other Indian groups. This study concludes that the presence of Indians in Java was closely linked to international relations involving political, religious, and economic factors, which played a significant role in sustaining the connection between Java and India. The political dynamics in India, including the rise and fall of the Chola kingdom, influenced the patterns of Indian trade activities in Java, providing new insights into the interaction between Java and India in the context of history and archaeology. Keywords: Inscription, Indian, Ancient Java, wargga kilalān, maṅilala dṛwyahaji Abstrak, Hubungan antara Nusantara dan orang-orang asing telah terjalin sejak awal Masehi. Salah satu kelompok yang datang adalah orang India. Hal ini yang kemudian melatarbelakangi perkembangan sejarah Hindu-Buddha di Nusantara. Kehadiran mereka pertama kali tercatat secara eksplisit dalam Prasasti Cane pada masa pemerintahan Airlangga dari abad ke-11 Masehi, dan terus berlanjut hingga periode Majapahit pada abad ke-15 Masehi. Catatan ini menunjukkan adanya hubungan yang erat dan berkelanjutan antara India dan Jawa. Penelitian ini bertujuan untuk memahami pengaruh kebudayaan India terhadap perkembangan politik, agama, dan ekonomi di Jawa selama periode tersebut serta mengidentifikasi asal-usul orang India, motif kehadiran mereka, dan pengaturan yang diterapkan oleh kerajaan-kerajaan di Jawa berdasarkan data prasasti. Metode penelitian yang digunakan adalah deskriptif-analitis dengan pendekatan kualitatif, yang mencakup pengumpulan, analisis, dan interpretasi prasasti dari abad ke-11 hingga abad ke-15 Masehi. Hasil penelitian menunjukkan bahwa prasasti Jawa Kuno menyebutkan berbagai kelompok India seperti kling, āryya, dravida, pandikira, karnnataka/karnnake, malyala, dan cwalika. Selain itu, ditemukan juga peran juru kling, yang bertugas mengurus orang-orang kling dan kelompok India lainnya. Kesimpulan dari penelitian ini adalah bahwa kehadiran orang India di Jawa terkait erat dengan hubungan internasional yang melibatkan faktor politik, agama, dan ekonomi, yang menjadi faktor penting dalam berlanjutnya hubungan antara Jawa dan India. Dinamika politik di India, seperti kejayaan dan keruntuhan Kerajaan Chola, mempengaruhi pola aktivitas perdagangan orang India di Jawa, sehingga memberikan wawasan baru tentang interaksi antara Jawa dan India dalam konteks sejarah dan arkeologi. Kata kunci: Prasasti, Orang India, Jawa Kuno, wargga kilalān, maṅilala dṛwyahaji